Research of the optical communications groups at University of Aveiro and Institute of Telecommunications - Aveiro Pole - da Rocha, J.F. (2012)
This paper summarizes the research activities of the optical communications group at University of Aveiro and Institute of Telecommunications – Aveiro pole. Several activities like clock recovery systems, both electrical and all optical, electrical equalizers for very high bit rate DST systems, post-detection filters for multigigabit optical receivers, soliton systems, simulation work on WDM, DST, EDFA and short pulse generation for high bit rate systems are presented.